2010
DOI: 10.1159/000290637
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Synapsis and Chiasma Localization: The Chicken or the Egg?

Abstract: In the present study, and as a sincere tribute from the Cytogenetics teams from Madrid to Professor Máximo Drets on his 80th birthday, we have analyzed and compared 3 different grasshopper species with different synaptic patterns, a standard pattern, a second pattern with synapsis restricted to the proximal regions, and a third pattern with synapsis restricted to the distal regions. In the 3 species we have thoroughly analyzed the relationships among cohesin axis morphogenesis, formation of double strand break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…Indeed, we previously reported that partial synapsis occurs but overall synapsis was strongly affected in axr1 -/-. Localized chiasma in restricted regions of some chromosomes that undergo pairing were also reported in various fungi, animals and plants [47,48] but these were rarely associated with CO clustering. Only the Arabidopsis pss1 and the Sordaria mer2-17 show such a phenotype, but to a lesser extent and with a less pronounced synapsis defect than in axr1 -/- [28,49].…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, we previously reported that partial synapsis occurs but overall synapsis was strongly affected in axr1 -/-. Localized chiasma in restricted regions of some chromosomes that undergo pairing were also reported in various fungi, animals and plants [47,48] but these were rarely associated with CO clustering. Only the Arabidopsis pss1 and the Sordaria mer2-17 show such a phenotype, but to a lesser extent and with a less pronounced synapsis defect than in axr1 -/- [28,49].…”
Section: Discussionmentioning
confidence: 80%
“…In mammals, this damage is typically signalled by the phosphorylation of histone variant H2AX (γH2AX), which rapidly expands to large regions of the nucleus (Mahadevaiah et al, 2001 ). Likewise, the onset of meiosis in grasshoppers is characterised by the presence of high levels of γH2AX, although with a much reduced number of RAD51 foci if compared to that found in mammals (Calvente et al, 2005 ;Viera et al, 2004a;Viera et al, 2009b ;Viera et al, 2010 ). In both cases, DNA repair may be related to the reduction or absence of transcription observed in leptotene.…”
Section: Figmentioning
confidence: 99%
“…grossum show a remarkable nuclear polarization of the axis maturation of cohesin subunits, and the location of γ-H2AX, which marks the sites of double-strand breaks, and RAD51, which is involved in homology search. This polarization was observed in both squashed and spread spermatocytes [31, 38, 39], and is maintained throughout prophase I along the chromosome regions that either are undergoing or are about to undergo synapsis (Fig 1C–1N). The identification of different early prophase I stages was carried out according to the degree of synapsis displayed by the shortest chromosomes and the chromatin morphology.…”
Section: Resultsmentioning
confidence: 92%
“…The identification of different early prophase I stages was carried out according to the degree of synapsis displayed by the shortest chromosomes and the chromatin morphology. According to these observations, it was proposed that the restricted distribution of recombination events along the chromosomal axes is responsible for the incomplete presynaptic homologous alignment and, hence, for the partial synaptonemal complex formation displayed by most bivalents[31, 38]. This proposal did not exclude the possibility that these processes may also be influenced and modulated by changes in chromatin organization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation